Baterai Ramah Lingkungan dari Limbah Serbuk Kayu Merbau (Intsia bijuga) dan Matoa (Pometia sp.) (Eco-friendly battery from Merbau (Intsia bijuga) and Matoa (Pometia sp.) sawdust) - Dessy Ernawati; Muliyana Arifudin; Susilo B Husodo (Masyarakat Peneliti Kayu Indonesia, 2019)
This research aimed to elucidate the potency of merbau and matoa sawdust as filler material of dry cell battery. The sawdust was ground, sieved to get a-80 mesh particle size and then made into paste. Then, the paste was put into the battery that its electrolyte has been removed previously. There were 40 batteries tested based on 3 treatments, namely wood species (A), charging time (B) and usage method (C). Each variable was tested with 5 replications. The battery was tested for its voltase generated and usage duration. The result indicated that the highest voltase was obtained from battery with matoa groundwood which was directly used for a stopwatch (1.99 volt), while the lowest voltase was found in battery with merbau groundwood which was kept for 20 minutes after charging, before it was used for the tested stopwatch (0.43 volt). Besides, the highest usage duration (˃20 mins) was found in both bio-batteries from merbau and matoa groundwood which were directly used after charging, with total 21 batteries. Sawdust of merbau and matoa has potency to be used as bio-battery, but their voltage generated and usage duration are still low, so several challenging problems are needed to be addressed.